Competitive Advantage; The Affecting Factors and Its Impact on Selling-In Performance (Studies on Patronage Outlets PT. Indosat Semarang) - Ana Kadarningsih (UBL, 2013)
There is fenomenal gap that amount of Indosat’s outlets have increased as41,76% in year 2007 until 2008,while Net Profit Margin have decreased as 18,66 % in year2008. Also there is research gap which saidthat competitive advantage have influence on performance sales, meanwhile other research result sellinginperformance has influence oncompetitive advantage. The purpose of this research is to test theinfluences of service qualityoutlet , differentiation, corporate image, quality of relationship with outlet ,environmentadaptability, on competitive advantage which is targeted to increase selling-in performance.The samples size of this research is 123 outlets of PT. Indosat. By using the Structural EquationModeling(SEM) with AMOS software , the results show that the service quality outlet,differentiation, corporateimage, quality of relationship with outlet, environment adaptabilityhave influence on competitiveadvantage which is targeted to increase selling-in performance.